Co-doping of Al and Bi to control the transport properties for improving thermoelectric performance of Mg2Si. (15th April 2016) - Kim, Gwansik; Kim, Jeongmin; Lee, Hwijong; Cho, Sungmee; Lyo, Inwoong; Noh, Sujung; Kim, Byung-Wook; Kim, Sung Wng; Lee, Kyu Hyoung; Lee, Wooyoung
Abstract: We investigated the thermoelectric properties of Al and Bi co-doped Mg2 Si polycrystalline bulks fabricated using a solid state reaction combined with the spark plasma sintering technique. Through controlled doping of Al and Bi, the power factor could be enhanced due to an increase in the Seebeck coefficient benefiting from an enhancement of the density of states effective mass. The lattice thermal conductivity was reduced due to intensified point-defect phonon scattering originating from the mass difference between the host Si atoms and Bi dopants. By these synergetic effects, the dimensionless figure of merit (ZT) of 1.02 was obtained at 873 K. Graphical abstract: